Budgeting in Uruguay Towards modern budgeting practices in Uruguay - Vammalle, Camila (OECD Publishing, 2019)
Uruguay is the only country in the world which has a five-year budget. A budget is prepared by each new government taking office and voted within 6 months of its swearing in, for the whole five-year government term. Each year, an annual revision ("budget update") takes place, where the government reports budget implementation to the Parliament and some adjustments to the coming year's budget can be made. Uruguay has done significant improvements in budget management in the last decade since 2005, achieving great results in terms of financial stability and funding predictability for spending institutions. The governance of the budget process has shifted, with the leadership for the budget process being now in the National Budget Unit and the Macroeconomic Assessment Unit (both located in the Ministry of Economy and Finance), and the Office of Planning and Budget (located in the Presidency) developing planning functions. While the new roles and responsibilities seem quite clear today, they are not yet institutionalised. This budget review aims to provide a detailed description of how Uruguay's budget institutions work today and present roles and responsibilities of each actor in the budget process. It also analyses Uruguay's budget practices in the light of OECD countries best practices, and proposes policy recommendations for further modernising Uruguay's budget process, in particular in the areas of aligning the budget with medium-term strategic planning and measuring results. EL codes: H50, H61, H80 Keywords: Uruguay, Five-year budget, Budget process, Strategic planning